Spirituality and Pedagogy: A Modest Proposal - Kelso, Priscilla Lasmarias (Silliman Journal, 2022)
The place of spirituality in higher education is increasingly Elie part of academic discourse as institutions confront the challenges and opportunities of the 21st century. Teaching and learning can be elevated to a higher plane through pedagogical practices that affirm human values and other essential elements that create a vital learning community. A vision of education as transformative and spiritually-based is particularly imperative at a time when academe struggles with fragmentation and cultural dissonance. How does a teacher create a climate of learning that transcends mere information-gathering? How does a student connect subject matter with the larger context of life? How can a university support curricular and instructional practices that nourish the spirit? All in all, the assumption is that teaching is a vocation and learning can be a bridge to wholeness.